2018
DOI: 10.1088/1361-651x/aae7c0
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation mobility and critical stresses at finite temperatures in molecular crystal cyclotetramethylene tetranitramine (β-HMX)

Abstract: Cyclotetramethylene tetranitramine (HMX) is an energetic material commonly found in plastic bonded explosives. Its crystallographic sensitivity to initiation and detonation has been linked to plastic slip in the various crystalline planes; shock directions which cannot accommodate substantial crystalline slip are expected to be more sensitive. In this work, we carry out constant stress-constant temperature molecular dynamics simulations of the motion of dislocations and characterize their behavior in the two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…The constitutive behavior of shear bands has been characterized as a function of the applied pressure and temperature using molecular simulations [31]. Furthermore, it was observed that fast moving dislocations in β‐HMX lead to strain localization [10, 27], which is consistent with reports for other crystals [32]. In fact, high pressure inhibits dislocation motion and promotes localization [10], which is thought to become the dominant plasticity mechanism under shock conditions.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…The constitutive behavior of shear bands has been characterized as a function of the applied pressure and temperature using molecular simulations [31]. Furthermore, it was observed that fast moving dislocations in β‐HMX lead to strain localization [10, 27], which is consistent with reports for other crystals [32]. In fact, high pressure inhibits dislocation motion and promotes localization [10], which is thought to become the dominant plasticity mechanism under shock conditions.…”
Section: Introductionsupporting
confidence: 73%
“…The loop is circular, which indicates that the mobility of all segments is approximately identical, independent of the angle between the Burgers vector and the dislocation line vector. The analysis of dislocation mobility reported in [27], which was performed using quasi-2D models with pre-existing dislocations indicates approximately iden-tical mobility for edge and screw dislocations moving in the negative direction. It also indicates stick-slip-type motion when loading is applied in the positive direction for both edge and screw.…”
Section: Pressure-dependent Critical Resolved Shear Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermal expansion coefficients determined by X-ray powder diffraction are ð0:29; 12; 2:3Þ � 10 À 5 K À 1 along the (a, b, c) axes and dðln bÞ=dT ¼ 2:6 � 10 À 5 K À 1 [48,49]. Recent works from Picu's group used the molecular dynamics simulations to investigate the dislocation motion and identify the potentially active slip systems in β-HMX at 0 K and finite temperatures [50]. Through indentation experiments and chemical etching, Sheen et al [24] reported two operative slip systems in β-HMX, namely, (001) [100] and (101) [10 � 1], based on the monoclinic crystallographic axis.…”
Section: Parameters Calibrationmentioning
confidence: 99%